Does winner’s curse hypothesis exist in explaining the underpricing phenomenon of Malaysian shariah-compliant IPOs? - Zunaidah, Sulong; Mohd Rahim, Ariffin; Nor Azizan, Che Embi (2017)
The Shariah-compliant status seems to be the major concern of the Securities Commission (SC) even though in reality the Malaysian stocks market players and the public listed companies (PLCs) owners are dominated by non-Muslims. The need for Shariahcompliant status seems more significant when the SC in 2004 introduced the pre-IPO Shariahcompliant list for new issues. This study aims to examine whether the short-run performance of Malaysian IPOs experience winner’s curse in a sample of 153 Shariah IPOs issued by Malaysian companies between January 2005 and December 2014. The study uses two alternative measures to test the presence of winner’s curse; allocation rate (ALLOCTj) or private place to institutional investors (DPRIVATE).The negative associations between both of these variables and initial returns suggest the existence of winner’s cursein the Malaysian IPOs regardless of Shariah status and level of Shariah compliance. This reveals a phenomenon where the high initial returns are purposely created by the issuers (by offering the IPOs at a deep underpricing) to allure the uninformed investors into the markets to replace the lack of interest from the informed investors.